ABO blood group does not impact incidence or outcomes of surgery for acute type A aortic dissection. (3rd March 2020) - Nozohoor, Shahab; Ahmad, Khalil; Bjurbom, Markus; Hansson, Emma C.; Heimisdottir, Alexandra; Jeppsson, Anders; Mennander, Ari; Olsson, Christian; Pan, Emily; Ragnarsson, Sigurdur; Sjögren, Johan; Tellides, George; et al.
Abstract: Objectives. To evaluate the distribution and impact of ABO blood groups on postoperative outcomes in patients undergoing surgery for acute type A aortic dissection (ATAAD). Design . A total of 1144 surgical ATAAD patients from eight Nordic centres constituting the Nordic consortium for acute type A aortic dissection (NORCAAD) were analysed. Blood group O patients were compared to non-O subjects. The relative frequency of blood groups was assessed with t-distribution, modified for weighted proportions. Multivariable logistic regression was performed to identify independent predictors of 30-day mortality. Cox regression analyses were performed for assessing independent predictors of late mortality. Results. There was no significant difference in the proportions of blood group O between the study populations in the NORCAAD registry and the background population (40.6 (95% CI 37.7–43.4)% vs 39.0 (95% CI 39.0–39.0)%). ABO blood group was not associated with any significant change in risk of 30-day or late mortality, with the exception of blood group A being an independent predictor of late mortality. Prevalence of postoperative complications was similar between the ABO blood groups. Conclusions. In this large cohort of Nordic ATAAD patients, there were no associations between ABO blood group and surgical incidence or outcomes, including postoperative complications and survival.